Bone-cartilage proportion in deformed ribs of male pectus excavatum patients. Issue 3 (4th May 2019) - Nagasao, Tomohisa; Aizezi, Niyazi; Noguchi, Masahiko; Morotomi, Tadaaki; Kudo, Hiroo; Kogure, Tetsukuni
Abstract: This study verifies the hypothesis that bone/cartilage proportion in deformed ribs of male pectus excavatum patients varies according to their ages. Anatomical evaluation of the thoraces was performed for 79 male pectus excavatum patients, referring to their three-dimensional computer-tomographic images. The patients were divided into Child Group (5–9 years old: n = 35); Adolescent Group (12–15 years old: n = 15) and Adult Group (18+ years old: n = 29). For each patient, the most concave point of the sternum was identified and the pair of ribs closest to the point were defined as Key Ribs. On each Key Rib, the most ventral point was defined as Prominent Point (PP); the junction between the bone and cartilage was defined as Costo-Chondral Junction (CCJ). The distances of these points from the spine were defined as Distance of Prominent Point (DPP) and Distance of Costo-Chondral Junction (DCCJ), respectively. The horizontal length of the Key Rib was defined as Rib Length (RL). Inter- and intra-group comparisons were performed for DPP/RL and DCCJ/RL. Inter-Group Comparison: DCCJ/RL is significantly smaller and DPP/RL is significantly greater in Adult Group than in Child Group, meaning CCJs shift medially and PPs shift laterally as patients get older. Intra-Group Comparison: In Child Group, DCCJ/RL is significantly greater than DPP/RL, meaning CCJs exist lateral to PPs. Contrarily, in Adult Group, DCCJ/RL is significantly smaller than DPP/RL, meaning CCJs exists medial to PPs. Bone/cartilage proportion in the concave part of the chest shifts according to patients' ages. To perform the Nuss procedure effectively, this age-related anatomical change must be taken into consideration.